PROSES REINTEGRASI SOSIAL ORANG YANG PERNAH MENGALAMI KUSTA (OYPMK) (Studi terhadap mantan penderita kusta di Desa Cangkring, Kecamatan Jenggawah, Jember) - Safira Wijayanti, Intan; wibowo, Purwo; Dewi Poerwanti, Sari; Santoso, Budhy; Nugroho Puspito, Agung (Multidisciplinary Journal, 2023)
Leprosy has various implications for sufferers starting from physical implications such as the condition of the skin changing to become rough and reddish spots appearing accompanied by decreased immunity, social implications which result in leprosy sufferers being indirectly excluded from the social system in society as well as discrimination, apart from that there are implications economically like losing your job. The condition of leprosy makes it difficult for a person to return to society even though he has been declared cured. There is a phenomenon that some people with leprosy who have experienced discrimination are able to reintegrate into the social system in society. Therefore, this research aims to describe the process of social integration of people who have experienced leprosy into society. The research method used was qualitative with a phenomenological approach on two people with leprosy who live in Cangkring Village, Jenggawah District. The results of this research state that there are two efforts to accelerate social reintegration for people who have experienced leprosy. Firstly, a strong desire based on aspects of cognition, mental and spirituality which is the main strength for a person to be able to push themselves back into society and change their perspective after experiencing leprosy. Second, social approach efforts are carried out consistently to form a communitybounding between someone who has experienced leprosy and the community in the surrounding environment. Success in the social reintegration process allows people who have experienced leprosy to be able to reintegrate into the social system and function socially as members of society such as interacting, starting a family, working and being able to overcome concerns about stigma and discrimination in the community.